Pentahelix Collaboration for the Development of Lappa Laona Tourism Village, Harapan Village, Tanete Riaja District, Barru Regency - Ulmi Sri Mutia; Andi Rachmat (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal